THE PERPETUAL STRUGGLE: HOW THE COEVOLUTION OF HIERARCHY AND RESISTANCE DRIVES THE EVOLUTION OF MORALITY AND INSTITUTIONS. Issue 2 (2021) - Buchanan, Allen
Abstract: Since the earliest human societies, there has been an ongoing struggle between hierarchy and resistance to hierarchy, and this struggle is a major driver of the evolution of moralities and of institutions . Attempts to initiate or sustain hierarchies are often met with resistance; hierarchs then adopt new strategies, which in turn prompt new strategies of resistance; and so on. The key point is that the struggle is typically conducted using moral concepts in justifications for or against unequal power and involves the stimulation of the moral emotions. Both parties to the struggle treat morality as a valuable strategic resource; and the dynamic of interaction between hierarchs and resisters generates changes in that resource. The hierarch/resister struggle is in part a competition between moral concepts and justifications, and that competition drives the emergence of new moral concepts and justifications, just as competition in other contexts generates innovations. Among the moral concepts generated by the struggle are the following: authority, legitimacy, aristocracy, the divine right of kings, the mandate of heaven, natural rights, civil and political rights, constitutionalism, the rule of law, sovereignty, collective self-determination, exploitation, oppression, and domination.